Contrasting Response of Two Dipolar Fluorescence Probes in a Leucine‐Based Organogel and Its Implications. Issue 11 (12th June 2015) - Soumya, Sivalingam; Seth, Sudipta; Paul, Sneha; Samanta, Anunay
Abstract The microenvironments of a leucine‐based organogel are probed by monitoring the fluorescence behavior of coumarin 153 (C153) and 4‐aminophthalimide (AP). The steady‐state data reveals distinctly different locations of the two molecules in the gel. Whereas AP resides close to the hydroxyl moieties of the gelator and engages in hydrogen‐bonding interactions, C153 is found in bulk‐toluene‐like regions. In contrast to C153, AP exhibits excitation‐wavelength‐dependent emission, indicating that the environments of the hydrogen‐bonded AP molecules are not all identical. A two‐component fluorescence decay of AP in gel, unlike C153, supports this model. A time‐resolved fluorescence anisotropy study of the rotational motion of the molecules also reveals the strong association of only AP with the gelator. That AP influences the critical gelation concentration implies its direct involvement in the gel‐formation process. The results highlight the importance of guest–gelator interactions in gels containing guest molecules.